PENGARUH KEDISIPLINAN TERHADAP KINERJA PEGAWAI PADA LEMBAGA PEMASYARAKATAN KELAS II A BULUKUMBA - Nurfika Rusyda; Uhud Darmawan Natsir; Zainal Ruma (Cross-border, 2022)
The Influence of Discipline on Employee Performance at Class II A Penitentiary A Bulukumba, thesis on the management study program of the Faculty of Economics and Business, Makassar State University. Supervised by Uhud Darmawan Natsir and Zainal Ruma. The role of human resources is a very important factor for an organization. Along with developments in today's reform era, all public organizations and state apparatus are required to be able to carry out their duties with full responsibility to achieve good performance. One of the factors that affect the performance is discipline. However, the phenomenon that occurs is that employee discipline is less effective, it can be seen from the hours of entry and return of employees who are not on time not in accordance with the provisions of working hours and employees still use long breaks. The purpose of this study was to determine the effect of discipline on the performance of employees at the Class II A Penitentiary in Bulukumba. The variables of this research are discipline (X) and performance (Y). The population in this study was specifically the prison guards (warriors) of the Class II A Penitentiary A Bulukumba, which amounted to 38 people. Data collection techniques were carried out using questionnaires, documentation, observation and interviews. While the analysis technique in this research is simple regression using SPSS (Statistical Product and Service Solution) software. The results showed that discipline had a positive and significant effect on the performance of employees at the Class II A Penitentiary in Bulukumba.